Sistema multienzimático inovador para a produção de ácido glicônico a partir de amido usando células inteiras de Aspergillus niger - Pucci, Emanoela Fernanda Queiroz (Universidade Federal de São Carlos, 2023)
Gluconic acid occurs naturally in a wide variety of foods, including fruit, honey, wine, rice, meat and other naturally fermented products. Because of its versatility and biodegradability, it has many applications in the food and beverage, pharmaceutical, and detergent industries. Although fermentation has been used for several decades, there are still drawbacks and challenges associated with the process. Fermentation processes often result in lower yields than chemical synthesis methods and require specific nutrients for the growth and metabolic activity of microorganisms. In addition, gluconic acid produced by fermentation can produce by-products, including other acids and organic compounds, which must be removed in the product purification stage, increasing the overall cost and complexity of the process. As an alternative to the fermentation processes, gluconic acid can be produced by whole-cell biocatalysis. Whole-cell biocatalysis uses intact microbial cells to perform specific chemical transformations or produce desired compounds. This approach differs from fermentation because microbial cells are used as biocatalysts under non-growth conditions. This study began with a literature review aimed at identifying and analyzing previous studies on the production of gluconic acid by whole-cell biocatalysis, as well as the microorganisms, substrates, and enzymes involved in this process. This review enabled the selection of starch, one of the most abundant natural polysaccharides, to produce gluconic acid. In the present study, an innovative single-step multi-enzymatic system for gluconic acid production from starch using whole-cells of Aspergillus niger associated with amylolytic enzymes was proposed. High yields of gluconic acid with high product purity were obtained, e.g., a gluconic acid concentration of 134.5 ± 4.3 g/L, a gluconic acid yield of 98.2 ± 1.3%, a biocatalyst yield of 44.8 ± 1.4 ggluconic acid/gwhole-cells and a product purity (~96%) were achieved during a 96 h reaction. Although the process was developed using starch as the raw material, the approach has the potential to be applied to other substrates or residues that can be hydrolyzed to glucose. Therefore, the proposed multienzyme system opens new perspectives for gluconic acid production by whole-cell biocatalysis.
An innovative multi-enzymatic system for gluconic acid production from starch using Aspergillus niger whole-cells
Keywords: Células inteiras; Biocatalisador; Aspergillus niger; Amido; Sistema multienzimático; Ácido glicônico; Enzimas amilolíticas; Whole-cells; Biocatalyst; Starch; Multienzyme system; Gluconic acid; Amylolytic enzymes; ENGENHARIAS::ENGENHARIA QUIMICA